2008
DOI: 10.1115/1.3002759
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Three-Dimensional Bioprinter: Construction of Cell Supporting Structures Using Hydrogel and State-Of-The-Art Inkjet Technology

Abstract: We have developed a new technology for producing three-dimensional (3D) biological structures composed of living cells and hydrogel in vitro, via the direct and accurate printing of cells with an inkjet printing system. Various hydrogel structures were constructed with our custom-made inkjet printer, which we termed 3D bioprinter. In the present study, we used an alginate hydrogel that was obtained through the reaction of a sodium alginate solution with a calcium chloride solution. For the construction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
202
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(203 citation statements)
references
References 8 publications
0
202
0
1
Order By: Relevance
“…Recently, several promising approaches have been reported. The most sophisticated approach to fabrication of alginate hydrogels involves inkjet printing [24,25] and photochemical UV photolysis of chelate calcium complex resulting in release of calcium cation and formation of ionic cross-links [26]. However, the problem of photodegradation of ionically cross-linked hydrogels has not been solved despite its importance for applications such as dynamically controlled cell detachment and migration as well as for 2D and 3D microfabrication.…”
Section: Open Accessmentioning
confidence: 99%
“…Recently, several promising approaches have been reported. The most sophisticated approach to fabrication of alginate hydrogels involves inkjet printing [24,25] and photochemical UV photolysis of chelate calcium complex resulting in release of calcium cation and formation of ionic cross-links [26]. However, the problem of photodegradation of ionically cross-linked hydrogels has not been solved despite its importance for applications such as dynamically controlled cell detachment and migration as well as for 2D and 3D microfabrication.…”
Section: Open Accessmentioning
confidence: 99%
“…This group also generated cell-laden tubular structures using HeLa cells. [87] Using their method, linear tubular structures with lengths in the centimeter range were achieved. Norotte and co-workers fabricated scaffoldless self-assembling 3D vessels using an extrusion-based bioprinter.…”
Section: Bioprinted Vesselsmentioning
confidence: 99%
“…[53] In these multicellular aggregates, the need for supporting gels or matrices is eliminated, the adverse effects 3D culture approach for generating a laminated cerebral cortex like structure from pluripotent stem cells. [57,58] Microfabrication Neuroprogenitor cells Microfluidic culture platform containing a relief pattern of soma and axonal compartments connected by microgrooves to direct, isolate, lesion, and biochemically analyze CNS axons [67,68] 3D bioprinting Primary human cortical neurons Discrete layers of primary neutrons in a RGD peptide-modified gellan gum [118][119][120] Intestine (Gut) Self-assembled Stem cells Identified intestinal stem cells and differentiated cells in vitro [59,60] Microfabrication Human epithelial cells Mimic contractility by using mechanochemical actuator [11,19,27,72] Liver Self-assembled Human stem cells 3D culture of self-renewing human liver tissue [61,62] Microfabrication Hepatocytes and fibroblasts Microengineered hepatic microtissues containing hepatocytes and fibroblasts [73][74][75][76][77] 3D bioprinting HepG2 and HUVEC Multilayered organ tissue model [96,[155][156][157] Vessel Microfabrication Rat brain endothelial cells 3D culture in microfluidic device [63][64][65][66] 3D bioprinting HUVECs and HUVSMCs Scaffold-less vessel formation using spheroid fusion [84][85][86][87][88][89][90][91]…”
Section: Engineering Technologiesmentioning
confidence: 99%
“…Having demonstrated that the print heads could deposit cells (Nakamura et al 2005), HeLa cells were encapsulated in 3D alginate hydrogels by this reactive printing approach (Nakamura et al 2006). In further work, the quality of the printed structures was improved by including viscosity enhancers such as PVA into the receiving bath and employing a high calcium chloride concentration, although this reduced cell viability to ~ 70% (Nishiyama et al 2009). In a more recent report, this reactive printing approach was reproduced with a custom piezoelectric inkjet head containing four separate nozzles (Arai et al 2011), although cell viability was not thoroughly investigated.…”
Section: Boland Et Al Explored Reactive Printing Approaches To Encapmentioning
confidence: 99%